Assignment 2: Mortality - Piotrowski, Martin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This is the second of a series of assignments that will ask you to research the demographic experience of a particular country. Use the country from your last assignment. If for some reason you no longer like the country from your last assignment, feel free to pick a new one from the list of available countries (see assignment 1 for list). If you wind up with a country about which you know nothing, at a minimum go to an atlas to see where it is and to an encyclopedia to get some simple basic background information. Otherwise you can simply use google to learn more about it.